Hypothyroidism risk associated with rheumatoid arthritis: A population-based retrospective cohort study. Issue 1 (7th January 2022) - Huang, Chung-Ming; Sung, Fung-Chang; Chen, Hsuan-Ju; Lin, Che-Chen; Lin, Cheng-Li; Huang, Po-Hao
Abstract : Abstract: Studies on the thyroid disease risk in patients with rheumatoid arthritis (RA) associated with comorbidities are limited. This population-based retrospective cohort study investigated the hypothyroidism risk in patients with RA and the role of comorbidities. We used Taiwan National Health Insurance Research Database to identify 16, 714 RA patients newly diagnosed in 2000 to 2008 and 66, 856 control persons without RA, frequency matched by sex, age, and index year. Incidence and the RA group to controls hazard ratio of hypothyroidism were estimated. The hypothyroidism incidence was 1.74-fold higher in the RA group than in controls (16.6 vs 9.52 per 10, 000 person–years), with the Cox method estimated adjusted hazard ratio of 1.67 (95% confidence interval = 1.39–2.00) after controlling for covariates. Near 75% of the study population were women, with the incidence 3.6-time higher than men in both groups. The hypothyroidism incidence increased with age, from 12.1 per 1000 person–years in 20 to 39 years to 20.0 per 1000 person–years in 60+ years in RA patients, higher than that in controls (7.17 vs 10.0 per 1000 person–years, respectively by age). Each comorbidity was related to an increased incidence and higher in the RA group than in controls. Among all comorbidities, stroke exerted the greatest impact in the RA group with an adjusted hazard ratio of 3.85 (95% confidence interval = 1.24–12.0). RA patients have an increased risk of developing hypothyroidism; this risk was pronounced in women and the elderly. RA patients should be closely monitored to prevent the development of hypothyroidism.